Innovation and Performance of MSMEs: A Systematic Literature Review - M. Syamsul Hidayat; Budi Utami; Eny Setyariningsih (Takaza Innovatix Labs Ltd., 2026)
MSMEs have been considered as one of the safety valves to overcome unfavorable economic conditions. Because MSMEs are growing and developing which can absorb labor. As a result, MSMEs are considered to be able to reduce unemployment. business is increasing. One way for companies/MSMEs to be competitive is to innovate. Many discussions are sometimes still debatable stating that innovation has a role that can affect company performance. Therefore, this article aims to provide a clearer understanding on the Role of Innovation on MSME Performance by conducting a systematic literature review of 12 relevant publication articles from 2015 to 2025.The results of the analysis identify that Innovation (product innovation, marketing innovation, process innovation and organizational innovation) has a significant influence on SME performance in various countries